Investigation and design of a slotted waveguide antenna with low 3D sidelobes - Maritz, Andries Johannes Nicolaas (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.